Advanced backend code optimization - Touati, Sid; De Dinechin, Benoit Dupont (London : ISTE ; Hoboken, New Jersey : Wiley, 2014)
"This book is a summary of more than a decade of research in the area of backend optimization. It contains the latest fundamental research results in this field. While existing books are often more oriented toward Masters students, this book is aimed more towards professors and researchers as it contains more advanced subjects. It is unique in the sense that it contains information that has not previously been covered by other books in the field, with chapters on phase ordering in optimizing compilation; register saturation in instruction level parallelism; code size reduction for software pipelining; memory hierarchy effects and instruction level parallelism. Other chapters provide the latest research results in well-known topics such as register need, and software pipelining and periodic register allocation."--
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed July 18, 2014).
Keywords: Compilers (Computer programs); COMPUTERS -- Computer Literacy; COMPUTERS -- Computer Science; COMPUTERS -- Data Processing; COMPUTERS -- Hardware -- General; COMPUTERS -- Information Technology; COMPUTERS -- Machine Theory; COMPUTERS -- Reference; Compilers (Computer programs); Electronic books